PEMBINAAN PENTINGNYA LITERASI MEDIA DAN INFORMASI BAGI SAMANERA DAN ATTHASILANI DI PADEPOKAN DHAMMADIPA ARAMA KOTA BATU - Rakay Indramayapanna (Indonesian Journal of Engagement, Community Services, Empowerment and Development, 2023)
Information technology today has developed rapidly. The development of information technology is marked by the many uses and utilization of digital-based media in the midst of community life. Apart from the benefits and negative impacts provided by information technology and digital media, information technology also contributes to changing one's behavior, even constructing reality according to the wishes of the newsmaker on the digital media. Furthermore, with the large number of digital media today, the information conveyed is also prone to bias so that it is easy to become hoax news. Based on these conditions, the public is considered necessary to not only know but also understand about media literacy so that it is not easily exposed to hoaxes even unknowingly becoming a hoax spreading society. Samanera and Atthasilani are people in Buddhist religious circles and the term refers to Buddhist monks. Media literacy skills are very important for Samanera and Atthasilani considering the activities carried out related to the implementation of counseling or lectures to the Buddhist community. This community service is packaged in the form of coaching on the importance of media and information literacy for samanera and atthasilani at Padepokan Dhammadipa Arama Batu City, East Java to provide guidance to samanera and atthasilani about the importance of media and information literacy so that it is expected to be able to increase awareness of true and incorrect information and become a society that can make good use of information technology